2009
DOI: 10.1167/iovs.08-3115
|View full text |Cite
|
Sign up to set email alerts
|

Optic Disc and Visual Field Changes after Trabeculectomy

Abstract: The study demonstrates that approximately one third of eyes continued to show progression of glaucoma at five years after trabeculectomy, as determined by trend-based analysis of ONH structural changes and VF sensitivity over time. The study suggests that the degree of IOP reduction after trabeculectomy may play an important role in the progression of glaucoma as detected by both functional and structural methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
2
21
1
1
Order By: Relevance
“…8 Our results showed a short-term improvement in global RNFL thickness after trabeculectomy. However, no definitive functional conclusions can be reached from these anatomical changes upon lowering IOP.…”
Section: Short-term Changes After Trabeculectomy M Figus Et Alsupporting
confidence: 60%
See 3 more Smart Citations
“…8 Our results showed a short-term improvement in global RNFL thickness after trabeculectomy. However, no definitive functional conclusions can be reached from these anatomical changes upon lowering IOP.…”
Section: Short-term Changes After Trabeculectomy M Figus Et Alsupporting
confidence: 60%
“…The lack of an absolute structure-function correlation may be due to the different levels of measurement noise displayed by the devices used to detect change, and it has been suggested that structural and functional methods can be considered as independent indicators of glaucoma damage. 8,17,18 Scanty literature is available on the association of functional and morphological changes after surgical IOP decrease. Only recently a paper with long-term data has been published, showing that one third of eyes continued to have progression of glaucoma at 5 years after trabeculectomy.…”
Section: Short-term Changes After Trabeculectomy M Figus Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Glaucoma is a progressive optic neuropathy that may cause irreversible visual field defects (1). Intraocular pressure (IOP) is a major risk factor for the development and progression of the disease (2).…”
Section: Introductionmentioning
confidence: 99%